STRESS AND COPING MECHANISM TOWARDS MENSTRUAL CYCLE DISORDER TO TEENAGER GIRL - Astuti, Vitaria Wahyu; Mesarini, Bisma Ayu (Jurnal Penelitian STIKES Kediri, 2013)
Everyone has experienced stress and become motivated to do coping mechanism. The purpose of this study to analyze the relationship between stress and coping mechanisms of the menstrual cycle disorders. The design used was cross sectional. The populations were grade IVÂ student at STIKES RS Baptis Kediri. The samples were 35 respondents using purposive sampling. The independent variable was coping mechanism. The dependent variable was level of stress towards period disorders. DataÂ were collected through questionnaires and observation. The analysis using